PENDAMPINGAN GERAKAN BAKTI SOSIAL MASYARAKAT DALAM MENENTANG HYDRO HEGEMONI DISUNGAI AKIBAT AKTIVITAS INDUSTRI - Nur Annisa Ramadhanti; Bayu Nurrohman (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Community activities will of course experience various threats and obstacles, in this case the discussion will be about the existence of social movement actions which result in misuse of water areas. The role of this movement is to provide education and assistance to the community to fight for their right to obtain clean water. The use of river water has become a core thing in life as a creature that needs water every day, so that its cleanliness and purity must be protected, apart from that, rivers become a field for various types of activities by humans, animals, ecology, and even industries. who is standing. Water pollution will not escape from the side-by-side between government and industry, so in this research it is intended that there is the emergence of a social movement of people who are in the midst of river water conditions which should be in the community's domain or riparian as the concept of hydro-hegemony is called for everyday life. -days not for self-rule interests by elites in local areas. The theoretical use of the concept of Hydro-Hegemony used in this research is taking the theory put forward by Mark Zeiton and Jeoren Warner as a study of hegemony in the waters of the River Watershed (DAS) and becomes a study of social movements in society, namely Jhon J Macionis who divides various the concept of social movements in terms of emergence, merger, bureaucracy and decline of social movements so that in their decline there are various types of classifications that are appropriate in resolving the case, namely success, failure, cooperation, pressure and/or as the main current in the social movement. In the methodology aspect, in this case, it is based on the opinions and concepts of Jhon W Creswell, his case study where researchers can have a direction to photograph, as in the case of opposing water pollution in the Cidurian river, Gembong Village, which is really water pollution and the interests contained in it, So this research is interesting because there is a theme about water politics which begins or is framed with water pollution actually occurring in the Cidurian River, Gembong Village, until in the end the results of the researchers made direct observations where the social movement of the community had to withdraw due to the interests of several actors. those in power in the area.